Changes in risky gambling prevalence among a New Zealand population cohort. Issue 2 (3rd May 2016) - Kruse, Kerri; White, Joanna; Walton, Darren K.; Tu, Danny
Abstract: Evidence suggests that problem gambling is an unstable state where gamblers move into and out of risk over time. This article looks at longitudinal changes in risky gambling and the factors associated with an increased risk (measured by the Problem Gambling Severity Index [PGSI]) in the current New Zealand context, which has experienced a doubling of the electronic gaming machine (EGM) market over the last two decades. Respondents from a nationally representative baseline sample ( n = 2672) were recontacted two years later to assess changes in gambling behaviours. Among the 901 respondents reached at follow-up, average gambling risk increased over time, and the prevalence of those who had at least some level of gambling risk (i.e. low-risk or greater) more than doubled (from 4.7% to 12.4%). The majority (80.2%) of those who were at risk at follow-up had not been at risk at baseline. Multivariate linear regression analyses show that the predictors of low to moderate increased risk include Pacific ethnicity; high neighbourhood deprivation status; baseline frequent, continuous gambler type; baseline PGSI status; and playing EGMs. These findings highlight the need to develop theories of gambling addiction trajectories and to identify the earliest point along the trajectory where public health interventions should occur.